2019
DOI: 10.3897/rrpharmacology.5.33831
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adverse side effects of corticosteroid therapy in children with nephrotic syndrome and methods of pharmacological correction

Abstract: Introduction: The article discusses the issues of the long-term glucocorticosteroid therapy in children with nephrotic syndrome that results in severe adverse side effects. Methods: This retrospective study included 89 case reports of patients with nephrotic syndrome, aged 1–18, who received treatment at Voronezh Regional Pediatric Hospital №1 in 1999–2014. The children’s BMI Z-score was calculated from neasured height and weight. The authors considered therapeutical complications revealed through cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The same study also revealed steroid-related toxicities such as Cushing's syndrome (44%), chronic gastroduodenitis (33%), hyperglycemia (11%), arterial hypertension (6%), and infectious diseases (6%). 27 Having a relapsing course of NS is associated with prolonged steroid treatment leading to an increased risk of steroid-related adverse effects. 21 Steroid-resistant NS is difficult to treat with 36-50% of the patients progress to end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also revealed steroid-related toxicities such as Cushing's syndrome (44%), chronic gastroduodenitis (33%), hyperglycemia (11%), arterial hypertension (6%), and infectious diseases (6%). 27 Having a relapsing course of NS is associated with prolonged steroid treatment leading to an increased risk of steroid-related adverse effects. 21 Steroid-resistant NS is difficult to treat with 36-50% of the patients progress to end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Los datos obtenidos no permiten estimar dirigídamente una prevalencia real de estas situaciones debido a la baja frecuencia con la que se controlaron los niveles de cortisol séricos y la glicemia capilar. La hiponatremia con o sin asociación a hipocalemia concomitante es un hallazgo común en insuficiencia adrenal primaria, pero no en aquellas de causa central, como las provocadas por el uso de glucocorticoides (25). La insuficiencia adrenal no tiene síntomas característicos hasta que un incremento en la tasa metabólica genera una crisis, la cual constituye una urgencia pediátrica con documentado impacto en la morbimortalidad (26).…”
Section: Discusión Y Conclusionesunclassified
“…Effect of inadvertent steroid use during COVID-19 lockdown in chronic illnesses in children Kapil Bhalla 1 , Anjali Verma 2 and Sanjiv Nanda 3 COVID-19 (SARS-CoV-2) pandemic is causing tremendous healthcare problems all around the world. It has extracted maximum toll on the elderly population with children being largely spared of its lethal effects.…”
mentioning
confidence: 99%
“…1 Various studies have discussed about development of various adverse effects in children requiring chronic steroid use in various illnesses. 2,3 The purpose of our study was to examine the current evidence for linking lockdown to adverse side effects of steroids in common childhood clinical problems.…”
mentioning
confidence: 99%